Pemanfaatan Radio Frequency Identification Mifare RC522 dan Arduino Sebagai Media Validasi Kehadiran Mahasiswa - Andriansyah Zakaria; Andesita Prihantara (Infotekmesin, 2020)
In every academic and student activity, data collection on student meetings is always done. General student data collection activities are still carried out manually by filling in the student attendance form. Besides being able to help and correct problems in lecturing activities, the manual presentation system is not practical in centralized recording and also increases human error in recording. The technology that can be used to add to these shortcomings is Radio Frequency Identification (RFID) in the presence of students. By utilizing RFID technology to approve and MySQL as a database, it is expected that student data collection and recording can be done easily and centrally. It can be concluded from the study that each RFID card used is a unique card identity that functions as a valid marker or identity for students or lecturers in conducting attendance.